Odpowiedź:
Poziom A
e)
a(b - 7)² = a(b² - 14b + 49) = 2(5² - 15 * 5 + 49) = 2(25 - 75 + 49) = 2 * (- 1) = - 2
f)
cd² - c²d = - 1 * (- 2)² - (- 1)² * (- 2) = - 1 * 2 - 1 * (- 2) = - 2 + 2 = 0
g)
p²(2r - 3) = (- 2)² * (2 * 6 - 3) = 4 * (12 - 3) = 4 * 9 = 36
Poziom B
e)
5p + (- pr + p²) * (- 2) = 5p - (pr - 2p²) = 5p - pr + 2p²
f)
2b + (6a - 9ab)/3 = (3 * 2b + 6a - 9ab)/3 = (6b + 6a - 9ab)/3 =
= 6b/3 + 6a/3 - 9ab/3 = 2b + 2a - 3ab
g)
xy - (- 3) * (x - 1) = xy - (- 3x + 3) = xy + 3x - 3
Poziom C
e)
4s³t + 6st³ - 2s³t + 5st³ = 2s³t + 11st³
f)
8c - 5d - 2cd + 5c - 8d + 2cd = 13c - 13d
g)
5w - 2z - 3 + 7w + 9 = 12w - 2z + 6
Poziom D
a)
3(a + 2b) - (b- 2a) + 9(b - a/3) = 3a + 6b - b + 2a + 9b - 3a = 2a + 5b
b)
- 6a + 2( 3a - b) - 4( - 2a + b) = - 6a + 6a - 2b + 8a - 4b = 8a - 6b
c)
2(x + 3y) - x( 3 - y) + 4y(1 - x) = 2x + 6y - 3x + xy + 4y - 4xy = - x - 3xy + 10y